Transforming UML class models - Simmonds, Devon Michael, author; France, Robert B., advisor; Ghosh, Sudipto, advisor; Bieman, James M., committee member; Florant, Gregory L., committee member (Colorado State University. Libraries, 2007)
In a model driven development (MDD) environment, developers create and evolve applications by creating models and transforming abstract models to more concrete models. To realize the benefits of MDD, model transformation languages are needed. The MOF 2.0 Query View Transformation (QVT) Language is an Object Management Group's (OMG) standard for specifying model transformations. QVT transformations are specified explicitly (in terms of) using instances of metamodel level classes. Using QVT to specify transformations on moderately-sized UML class models results in large object-level specifications that can be tedious to read and understand. This dissertation presents a language for specifying class model transformations at a higher level of abstraction than the level of instances of metamodel classes. The language leverages the UML class model notation, and is used to create transformation schemas that consist of transformation directives. An interpreter for performing the transformation is also presented. The interpreter performs the transformation by processing the directives found in the transformation schema. The interpretation algorithm is described in this dissertation. To demonstrate the use of the transformation technique, platform-independent class models describing transaction and distribution features are transformed into platform-specific class models describing CORBA and Jini realizations of the features.
Keywords: computer science